Anaesthesia for thoracic surgery. Issue 12 (December 2017) - Simpson, William
Abstract: Thoracic anaesthesia is an expanding and evolving sub-speciality. This article will focus primarily on the anaesthetic management of major lung resections, procedures which are generally performed for malignant disease and which can confer significant mortality and morbidity. The equipment needed and ventilatory strategies during one lung anaesthesia will be discussed and the important changes in respiratory physiology that occur will be looked at in detail. Recent advances in pain management necessitate that postoperative analgesic regimens are covered in some depth. There has been an increase in the number of video-assisted thoracoscopic surgery (VATS) cases and the merits and anaesthetic implications of VATS procedures are reviewed.